Sang Bayu Kinabalu Restaurant - Amir Hamja, Noraishah; Matali, Noorasyikhin; Ali, Nurulin; Maideh, Emillda Dorra; Ajin, Annette Evangeline (2014)
Sang Bayu Kinabalu Restaurant is the restaurant which provide or serve the traditional foods Sabahan which is focus on three main races in Sabah namely Kadazandusun, Bajau and Bugis. This idea of business was establish only after we having a brainstorming and some observation among our group members. Before we came out with this idea of proposal, we already go for observation and some study about the development of tourism industry in Sabah. From this, we saw the opportunities that we can get from the development of tourism industries. This business proposal that we produce includes four areas which is administration plan, marketing plan, operational plan and financial plan. In administration plan, we will start about the background of our business, background of our partners, the logo of Sang Bayu Kinabalu Restaurant, the mission and vision and many more. For the marketing plan, there will be having such thing like market size, target market, our competitor, market strategies and the most important things is our sales forecast. In operational plan, there will be include how we carry out our business, what are the equipment that we going to have, how many workers will be hired for this business, our business hour and many more. At the end of every section, there will be a budget for every plan. This budget will be included in our financial structure. Financial plan is the most important part in business proposal because from this we can see either the business can give us profit or vice versa. On this financial plan, we will have our income statement balance sheet, implementation cost, our cash flow and many more.